Marrow Assessment for Hemophagocytic Lymphohistiocytosis Demonstrates Poor Correlation With Disease Probability. Issue 1 (1st January 2014) - Ho, Caleb; Yao, Xiaopan; Tian, Ligeng; Li, Fang-Yong; Podoltsev, Nikolai; Xu, Mina L.
Abstract: Objectives: To evaluate the amount of hemophagocytosis in 64 marrow core biopsy specimens and aspirates from 58 patients with clinical suspicion for secondary hemophagocytic lymphohistiocytosis (HLH) or reported findings of hemophagocytosis. Methods: A review of medical records assigned patients to a low-risk (45 patients) or high-risk (13 patients) HLH group, and association with histologic findings was examined using the Fisher exact test. Results: The amount of hemophagocytosis in aspirate or the core biopsy specimen did not correlate with disease probability ( P = .17 and P = .63, respectively). Of the clinical/laboratory criteria assessed, the most significant correlations with HLH were highly elevated ferritin ( P = .01), cytopenias ( P = .02), and fever ( P = .009). Conclusions: Our findings indicated that marrow histologic findings alone do not reliably predict the probability of HLH, and an isolated finding of hemophagocytosis, even when present in a high amount, lacks specificity for HLH.